The data mirage : why companies fail to actually use their data - Vargas Ugarte, Rubén, 1886-1975 (Big data and business analytics., 2021)
The data mirage: why companies fail to actually use their data is a business book for executives and leaders who want to unlock more insights from their data and make better decisions. The importance of data doesn't need an introduction or a fancy pitch deck. Data plays a critical role in helping companies to better understand their users, beat out their competitors, and breakthrough their growth targets. However, despite significant investments in their data, most organizations struggle to get much value from it. According to Forrester, only 38% of senior executives and decision-makers "have a high level of conﬁdence in their customer insights and only 33% trust the analytics they generate from their business operations."